Replating protocol for human induced pluripotent stem cell–derived cardiomyocytes - Koç, Arzuhan; Çağavi, Esra (Humana Press Inc., 2022)
Human induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CM) create an unlimited cell source for basic and translational cardiac research. Obtaining hiPSC-CM culture as a single-cell, monolayer or three-dimensional clusters for downstream applications can be challenging. Thus, it is critical to develop replating strategies for hiPSC-CMs by evaluating different enzymatic or nonenzymatic reagents for dissociation and seeding on different coating materials. To reseed hiPSC-CMs with high viability and at structures desirable for the downstream applications, here we defined optimized protocols to dissociate hiPSC-CMs by using collagenase A&B, Collagenase II, TrypLE, and EDTA and reseeding on various matrix materials including fibronectin, laminin, imatrix, Matrigel, and Geltrex. By the replating methods described here, a single cell or cluster-containing hiPSC-CM cultures can be generated effectively.
Keywords: Cardiac Differentiation; Cardiomyocytes; Cell Dissociation; Human Induced Pluripotent Stem Cells; Replating Cardiomyocytes